Histochemical quantification of glutathione contents in guard cells of Arabidopsis thaliana - Md. Sarwar, Jahan; Yoshimasa, Nakamuraa; Yoshiyuki, Murata (2011)
: Glutathione (GSH), one of the most abundant low molecular-weight thiol compounds, maintains redox homoeostasis in plants. To measure GSH content in guard cells of Arabidopsis thaliana, we have developed a technique to quantify the GSH content in guard cells using the staining dye monochlorobimane (MCB). The fluorescent intensity of glutathione S-bimane (GSB) gradually increased in guard cells with increasing incubation time and reached steady state 2 h after epidermal tissues were treated with MCB. The guard cells contained larger amount of GSH content than other cells of the leaves except trichome cell. MCB staining showed that guard cells of ch1-1, a GSH deficient mutant, accumulated significantly lower GSH content than that of wild type guard cells. When the guard cells were treated with 1-chloro-2,4- dinitrobenzene to reduce GSH content in the guard cells, the GSB fluorescence in the guard cells was abolished. In addition, GSH monoethyl ester restored GSH level in the guard cells of ch1-1 mutant plants. These results suggest that GSH content in guard cells can be quantified using MCB dye.